New constraints on the tectono‐magmatic evolution of the Tidding‐Mayodia ophiolites, eastern Himalaya, northeast India. Issue 2 (22nd November 2021) - Singh, Athokpam Krishnakanta; Dutt, Amrita; Nayak, Bibhuranjan; Bikramaditya, Raj Kumar; Oinam, Govind; Thakur, Satyajeet S.; Srivastava, Rajesh K.; Khogenkumar, Shoraisam; Kumar, Manoj
Abstract : The Tidding‐Mayodia ophiolites (TMO) exposed along the Lohit and Dibang river valleys in eastern Himalaya that have been considered as the extension of the Indus‐Tsangpo Suture Zone ophiolites are revisited to review their petrogenetic‐tectonic origin. The ophiolites consist of depleted harzburgite and dunite with lesser amounts of mafic rocks (gabbro intrusives, mafic dykes) and carbonates. The serpentinized peridotites consist of antigorite, lizardite, olivine, Cr‐spinel, and bastite with minor sulfide minerals. From SEM‐EDS studies, sulfide minerals were observed to be associated mainly with magnetites. The main sulfide mineral is pentlandite with minor millerite that exists as inclusions inside the pentlandite grains. Elemental mapping of these sulfides shows that they are mainly Ni‐(Co‐)‐bearing sulfides. The olivines are highly forsteritic (Fo = 95–96) while the Cr‐spinels show distinct Cr‐magnetite rims with a chromite core (Cr# = 93). The serpentinized peridotites have whole‐rock compositions of SiO2 <47 wt% and high MgO (>36.37 wt%) and low Al2 O3 (<1.21 wt%), CaO (<0.82 wt%), indicating the depleted nature of the parent rocks. Highly fractionated LREEs as compared to HREEs [(La/Yb)N = 2.62–13.22], and REE and Cr spinel chemistry modelling suggests that the studied peridotites have formed from 22% partial melting of a depleted spinel lherzolite source which later underwent interactions with a high‐temperature silicate melt that caused enrichment in LREE and Cr of spinels. The parental melt compositions of Cr spinel yield their formation during arc tectonism (Al2 O3melt = 6.28–7.65 wt%, FeO/MgO = 1.00–1.33). Furthermore, Mn and Zn concentrations in spinels, the occurrence of Cr magnetite rim in Cr‐spinels, presence of secondary olivine with higher Fo ( 98), and occurrence of low‐temperature re‐equilibrated sulfide minerals, indicate that the rocks were subject to low‐temperature metamorphism. Based on this evidence, combined with data from previous studies, a tectonic model has been proposed for the genesis of the studied ophiolites. This model shows that the ophiolites have formed from the entrapment of depleted N‐MORB mantle in the mantle wedge of an intra‐oceanic subduction zone. During the nascent forearc regime, this mantle wedge underwent interactions with high‐temperature melts, which caused changes in their chemistry. Moreover, the rocks underwent interactions with low‐temperature fluids in the mature forearc, which caused the formation of sulfides and metamorphozed these rocks. Abstract : The Tidding‐Mayodia ophiolites (TMO) of the eastern Himalaya is a remnant of the oceanic lithosphere and considered part of the Indus‐Tsangpo Suture Zone ophiolites. Peridotites in TMO exhibit high MgO (>36.37 wt%) and SiO2 (>42.52 wt%) indicating involvements of secondary melts in their formations. Their refractory nature is indicated by the high Fo content ( 95) of the olivine grains as well as by the parental melt composition of Cr‐spinels (Al2 O3melt = 6.28–7.65 wt%, FeO/MgO = 1.00–1.33). These peridotites underwent interactions with low‐temperature fluids in the mature forearc, which caused the formation of sulfides and metamorphozed these rocks. Our study suggest that the TOM ophiolites were generated in the nascent forearc of an intra‐oceanic subduction zone followed by interaction with high‐temperature silicate melts and low‐temperature metamorphic fluids.